The Use of Dietary Interventions in Pediatric Patients - Shirin Madzhidova; Lusine Sedrakyan (MDPI AG, 2019)
Complementary and alternative treatment approaches are becoming more common among children with chronic conditions. The prevalence of CAM use among US adults was estimated to be around 42% in 2015 and around 44% to 50% among adults with neurologic disorders. Studies demonstrate that children with certain chronic illnesses such as asthma, cancer, genetic disorders, attention-deficit/hyperactivity disorder (ADHD), and other neurodevelopmental disorders are treated with complementary and alternative treatments at higher rates. Dietary therapies are gaining increasing popularity in the mainstream population. Although the majority of “fad” diets do not have enough supporting evidence, some dietary therapies have been utilized for decades and have numerous published studies. The objective of this review is to describe the dietary interventions used in children with the specific chronic conditions, to evaluate their efficacy based on published data and to encourage pharmacist involvement in the management and care of such patients.